Yeasts from Tierra Del Fuego Province (Argentina): Biodiversity, Characterization and Bioprospection of Hydrolytic Enzymes - Cavello, Ivana Alejandra; Bezus, Brenda; Martinez, Adalgisa; Garmendia, Gabriela; Vero, Silvana; Cavalitto, Sebastian Fernando (Geomicrobiology Journal)
Antarctic and sub-Antarctic regions are – with Polar Regions, mountains and the deep sea – the most extreme environments on Earth because of its low temperatures, dryness, high incidence of solar radiation and low nutrient availability. Nevertheless, microorganisms have successfully colonized these regions. In this study, culturable yeasts from soil samples collected from two different locations, a human-impacted area (Encerrada Bay) and a largely pristine and naturally vegetated area near Lago Escondido city (54 390 000S, 67 460 4800W) from Tierra del Fuego province, Argentina were identified and characterized at different levels. They were characterized and classified as psychrotolerant and were considered as moderately halotolerant because of their ability to grow in the presence of 1.5 M of NaCl. Yeasts from phylum Ascomycota were affiliated to five genera: Candida, Yarrowia, Debaryomyces, Nadsonia, and Wickerhamiella, whereas from phylum Basidiomycota yeasts were affiliated to six genera: Naganishia, Rhodotorula, Leucosporidum, Tausonia, Cystofilobasidium, and Apiotrichum. Most of the yeasts demonstrated at least one extracellular enzymatic activity (mainly b-glucosidase, esterase, and protease activities). One isolate identified as Tausonia pullulans showed significant activity across the eight enzyme types tested. In light of these findings, Tierra del Fuego province could be considered as a cold environment with a potential source of cold-adapted yeasts producing industrially relevant cold-active enzymes. Fil: Cavello, Ivana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Bezus, Brenda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de ...